2015
DOI: 10.1038/ejcn.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-containing beverage intake in toddlers and body composition up to age 6 years: The Generation R Study

Abstract: Higher SCB intake at 13 months was associated with higher BMI up to age 6 years in girls but not in boys. Our results imply that the unfavorable effects of SCB intake start early in life and that dietary advice regarding limiting SCB intake should already be given early in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
2
31
2
Order By: Relevance
“…Our results are in line with the findings of Slade et al [28], who reported that 32% of infants younger than six months drank SSBs regularly. Leermakers et al [29] recently showed that the heavy consumption of SSBs begins in infancy. Children with the highest intakes of SSBs are more likely to be overweight or obese than children with lower intakes of such drinks [12,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with the findings of Slade et al [28], who reported that 32% of infants younger than six months drank SSBs regularly. Leermakers et al [29] recently showed that the heavy consumption of SSBs begins in infancy. Children with the highest intakes of SSBs are more likely to be overweight or obese than children with lower intakes of such drinks [12,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Because we previously identified differences in associations of diet with body composition between boys and girls [29, 30], we evaluated the statistical interaction with sex by adding the product term of child sex and each of the dietary patterns to the multivariable models on FMI and FFMI. Statistical analyses were performed using SPSS version 21.0 (SPSS Inc., Chicago, IL, USA) and SAS version 9.1 (SAS Institute, Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Because the FFQ was developed and validated for Dutch children, we performed sensitivity analyses in Dutch children only. Previous studies suggest that the influence of several nutrients in early life might differ between boys and girls (38,39). Furthermore, it is suggested that nutrients involved in the 1-carbon metabolism, such as folate, might interact with MTHFR polymorphisms (40).…”
Section: Methodsmentioning
confidence: 99%